Bibliometric Analysis of Islamic Education Management - Eli Sabrifha (Fakultas Tarbiyah dan Keguruan, 2022)
The purpose of this study is to describe the concentration of topics on Islamic education management in the future in order to gain a full understanding. The google schoolar data source is used because it is considered to have the most number of articles discussing Islamic education management. As a bibliometric analysis tool, the VOSviewer software is used to show the author's network. The search was carried out on October 13, 2022 inputted with the keyword